Essays on foreign direct investment and international trade - Kett, B (2020)
This thesis consists of three standalone chapters split between two main topics that speak to the effects of using unilateral, national policies in place of pursuing international cooperation. The first topic focuses on the recent move towards increased trade barriers and their effects on labour demand, and the second addresses the utilisation of tax policy to attract internationally mobile capital. Chapters 1 and 2 cover the first topic, using high frequency data on the near universe of job adverts posted online in the United Kingdom and United States to investigate the relationship between trade barriers and labour demand. Chapter 1 specifically studies the impact of the Brexit referendum on labour demand, with the emphasis placed on potential future trade barriers between the UK and European Union. The main results show that commuting zones that were more exposed to potential barriers on professional services exports saw a differential decline in online job adverts in the period after the referendum, particularly after the middle of 2018, and in months when there was heightened uncertainty about trade policy. No such effect is found for commuting zones than were more exposed to future tariff barriers of goods. Chapter 2 investigates the impact of the 2018 tariff increases on US labour demand, in this case focusing on the actual tariffs that were applied during this period rather than expectations about the future. The analysis finds that commuting zones that were more exposed to tariffs on imported inputs, as well as those more exposed to retaliatory tariffs, saw a differential decline in online job adverts in 2018. No equivalent positive effect was found for tariffs on imports competing with US production. Chapter 3 relates to the second topic, analysing the impact of corporate tax rates and tax holidays on inward greenfield Foreign Direct Investment (FDI) using a new global dataset compiled by the World Bank. Higher corporate tax rates are shown to have a negative impact on FDI attraction, but there is no robust evidence that tax holidays are effective.